Double Face Evidentials in German: Reportative ‘sollen’ and ‘wollen’ in Embedded Contexts - Schenner, Mathias (Proceedings of Sinn und Bedeutung, 2019)
The evidential (reportative) uses of the German modals sollen ‘should’ and wollen ‘want’ are typically given a purely modal analysis that yields correct predictions for unembedded cases, but fails to account for many embedded occurrences. Based on a corpus and a questionnaire study it is argued that these modals can receive three distinct kinds of interpretation when they occur embedded in clausal complements (partly dependent on the embedding predicate). A revised analysis of reportative sollen is offered that involves a reportative presupposition and a conditionally activated assertive component.